An asymmetric 2, 3-fluoranthene imide building block for regioregular semiconductors with aggregation-induced emission properties. Issue 4 (6th January 2022) - Sun, Xianglang; Liao, Ming-Yun; Yu, Xinyu; Wu, Ying-Sheng; Zhong, Cheng; Chueh, Chu-Chen; Li, Zhen; Li, Zhong'an
Abstract : A new electron-deficient 2, 3-fluoranthene imide unit was easily synthesized through a one-pot reaction for constructing small molecule regioregular semiconductors with good carrier transport ability and strong solid-state emission. Abstract : For organic semiconductors, the development of electron-deficient building blocks has lagged far behind that of the electron-rich ones. Moreover, it remains a significant challenge to design organic molecules with efficient charge transport and strong solid-state emission simultaneously. Herein, we describe a facile synthetic route toward a new π-acceptor imide building block, namely 2, 3-fluoranthene imide, based on which four regioregular small molecules (F1–F4 ) are synthesized by tuning the imide orientations and the central linkage bridges. All molecules exhibit attractive aggregation-induced emission (AIE) characteristics with strong far-red emission in the powder state, and F3 shows the highest photoluminescence quantum yield of 5.9%. F1 and F3 with a thiophene bridge present an obvious p-type characteristic, while for F3 with an outward imide orientation, the maximum hole mobility from a solution-processed field-effect transistor (FET) device reaches 0.026 cm 2 V −1 s −1, being ∼10 4 times higher than the value of F1 with an inward imide orientation. By using a fluorinated thiophene bridge, the resulting F2 and F4 can be turned into n-type semiconductors, showing an electron mobility of ∼1.43 × 10 −4 and ∼3.34 × 10 −5 cm 2 V −1 s −1, respectively. Our work not only demonstrates that asymmetric 2, 3-fluoranthene imide is a promising building block for constructing organic materials with high carrier mobility and strong solid-state emission, but also highlights the importance of regioregular structures in the materials' properties.